Brochure on Public Sector Undertakings Andhra Pradesh - Planning Commission (Planning Commission, 1969)
The Andhra Pradesh Text book Press is functioning since 1958 on commercial lines under the control of the Education Department. Its functions are printing and distribution of Nationalised Text books throughout the State. Ten categories of text books have been nationalised for use during 1969-70 in addition to the changing Telugu Reader I. 126 categories of text books have been so far nationalised in Telugu, English, Hindi, Sanskrit and Urdu, Text looks in Telugu language have been nationalised for all classes from I to X and some books in English and Urdu media have been nationalised.
Government of Andhra Pradesh